VD_FINDINFO Décision / 2012 / 988 vom 26. September 2012 - VD Tribunal cantonal (2012)
CLASSEMENT DE LA PROCÉDURE, ABUS DE CONFIANCE, ESCROQUERIE | 138 CP, 146 CP, 310 CPP (CH), 393 al. 1 let. a CPP (CH)